2008
DOI: 10.1097/yco.0b013e3282f52851
|View full text |Cite
|
Sign up to set email alerts
|

New generation antipsychotic drugs and compliance behaviour

Abstract: A decade of clinical experience and research indicates that compliance behaviour has only marginally improved since the introduction of second generation antipsychotic drugs. Noncompliance in schizophrenia is a complex maladaptive pattern of behaviour determined by personal beliefs, illness-related factors, social attributes and health system variables. The reinforcing value of antipsychotic drugs may be less relevant in enhancing treatment compliance and influencing the natural history of schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…While antipsychotic medication still represents the treatment of choice for schizophrenia, the objective impact on symptoms achieves only a medium-effect size in comparison with placebo (Leucht et al 2009). Moreover, approximately 20-30 % of patients are resistant to antipsychotics (Elkis, 2007) and medication compliance remains low, even in the era of atypical antipsychotic medication (Byerly et al 2007 ;Voruganti et al 2008). The 1-year relapse rate under atypical neuroleptics is 15 % compared with 23 % under conventional agents and 33 % under placebo (Leucht et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…While antipsychotic medication still represents the treatment of choice for schizophrenia, the objective impact on symptoms achieves only a medium-effect size in comparison with placebo (Leucht et al 2009). Moreover, approximately 20-30 % of patients are resistant to antipsychotics (Elkis, 2007) and medication compliance remains low, even in the era of atypical antipsychotic medication (Byerly et al 2007 ;Voruganti et al 2008). The 1-year relapse rate under atypical neuroleptics is 15 % compared with 23 % under conventional agents and 33 % under placebo (Leucht et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Poor adherence to medication is associated with psychiatric early readmission. If the treatment program seeks to decrease the incidence of early readmission, greater attention should be provided to help the patients to recognize their own symptoms and understand their illness with the aim to improve medication adherence [16]psychiatric mental health nursing and advanced practice registered nurse PMH-APRNs assess, diagnose and treat individuals and families with psychiatric disorders or the potential for such disorders using their full scope of therapeutic skills including the prescription of medication and administration of psychotherapy .PMH-APRNs often own private practices and corporation as well as consult with groups, communities and corporation [17].Therefore, healthcare providers need to recognize the factors associated with readmission rate among hospitalized mentally ill patients so they can be prevented. A better understanding of the factors related to readmissions needed to help better management and early intervention.…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Determining the factors that contribute to the readmission phenomenon may assist in the development of programs and policies to prevent readmission, improve patient care and quality of life, as well as reduce the costs of care, especially in care models with reduced availability of beds and greater restrictions for caring for mentally ill patients [16].Moreover severe mental illnesses are often characterized by a chronic relapsing course that may require repeated hospital admissions, several potential predictors of readmission has identified following a psychiatric hospitalization as poor access to past-discharge outpatient services, younger age, more severe clinical diagnosis (e.g. schizophrenia or bipolar disorder), lack of supportive significant others (being unmarried, divorced, or widowed), medication non-adherence and poor access to adequate housing [13].…”
mentioning
confidence: 99%
“…One of the major sources of non-compliance is the highly unpleasant side-effect profile of both typical and atypical antipsychotics [22,23] . As might be expected, drugs with different side-effect profiles have different rates of noncompliance and associated direct costs [22] .…”
Section: Schizophreniamentioning
confidence: 99%
“…EPS are unpleasant for obvious reasons, and elevation of serum prolactin can lead to numerous sexual side effects, which can be among the most unpleasant side effects of antipsychotic treatment [24,25] . It was hoped that the newer generation atypical antipsychotics would improve patient compliance, but most studies that compare typicals and atypicals with respect to patient compliance did not detect any difference [17,23] . This is probably due to their own unique side effects -for example, the vast majority of patients experiencing weight gain, a side effect of many of the atypicals, reported that to be problematic [16,26] .…”
Section: Schizophreniamentioning
confidence: 99%